Fundamental problems of technology of complex multicomponent mixes division - А. K. Frolkova; L. А. Serafimov (Тонкие химические технологии)
Article is devoted to analysis of researches in the field of fundamental bases of technology of complex multicomponent mixes division for last 40 years